Principal Policy on Students' Use of Social Media in an Effort to Improve Learning Interest (Case Study of MAS Al-Washliyah Johor) - Wulandari, Tiwi; Nasution, Inom (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract: The purpose of this study was to see how the principal of MAS Alwasriya Johor manages the use of social media to increase students' learning interest. Social media is an online platform that allows people to communicate, collaborate, share, communicate, and build real social relationships. This descriptive field study used a qualitative methodology. Based on the survey results, in the 2022/2023 academic year, all MAS Al Wasriya Johor students were more active on social media, especially to upload daily activities and as a learning tool, although they often used cellphones during learning. I feel it is being used. The Principal took action, including prohibiting the use of cellphones during learning and ordering teachers to confiscate cellphones used during learning. This strategy was very effective, as evidenced by the reaction of students who left their cellphones in the classroom and secretly used social media during recess. Keywords: Head of Madrasah, Social Media, Learning Interest